Assessment Of Cardiovascular Disease Risk by Using Framingham Risk Equation Amongst the Residents of Ahmedabad City - Parikh, Sonal; Patel, Manish; Tiwari, Hemant; Bala, D V; Joshi, Bhavin (National Journal of Community Medicine, 2013)
Introduction: Coronary heart disease (CHD) risk estimation tools are a simple means of identifying those at high risk in a community and hence a potentially cost-effective strategy for CHD prevention in resource-poor countries. Aim: To estimate 10 years risk for hard CHD among the urban population by using Framingham Heart Study produced sex-specific coronary heart disease (CHD) prediction functions and to find out correlates of CHD risk in study population. Methodology: Present community based descriptive study was carried out in 1133 residents of south zone of Ahmedabad Municipal Corporation, Gujarat state (India), age 20 years or more without any previous history of CVD. Framingham Heart Study produced simple model with office based non laboratory predictors was used to assess for estimating 10 years risk of developing hard coronary heart disease . Results: The median 10-year probability of CHD was 2.9% (5.6% for men and 1.8% for women). One third (33.4%) population above 30 years had CVD risk 20% or more. Males had significantly higher CVD risk as compared to females (20% of males & 4.5% of female had high CVD risk). Cardiovascular disease risk was also person with inadequate sleep & in executives. Conclusion- Higher risk in males & unskilled worker was mainly due to tobacco addiction while in executives it was mainly due to diabetes & obesity.